Implementasi Labview Untuk Pemantauan Pemakaian Energi Listrik - Muhammad Yusuf Yunus; Marhatang Marhatang (Muhammadiyah University, Sidoarjo, 2018)
In conventional electric measurement devices, measurements are made on the use of electrical energy as a whole where consumers can only see information on the results of the use of electrical energy by looking at the total power consumption amount indicated on the meter kWh meter. Based on the above problems, the author aims to raise the title